Volume 5a: 17th International Conference on Design Theory and Methodology 2005
DOI: 10.1115/detc2005-85438
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Product Usage Context on Consumer Product Preferences

Abstract: We present a framework for understanding product usage context and its impact upon customer needs and product preferences. We conduct customer interviews with two sets of representative products from the functional families of "mobile lighting" and "food boiling" products. Customer interviews lead to identification and characterization of distinct product usage contexts. Interactive surveys measuring customer product choice support the hypothesis that customer product preferences differ for each usage context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…More importantly, this study helps developers decide whether the product's technical function or the user, through his/her tasks, should carry out active roles. Work in this area includes methods to describe users' needs, their use-processes [15] and the context-of-use [16].…”
Section: User and Task Analysismentioning
confidence: 99%
“…More importantly, this study helps developers decide whether the product's technical function or the user, through his/her tasks, should carry out active roles. Work in this area includes methods to describe users' needs, their use-processes [15] and the context-of-use [16].…”
Section: User and Task Analysismentioning
confidence: 99%
“…The recent scholarship has started modelling user habits. Green et al (2005) emphasized the importance of understanding and representing usage contexts for simulating a product's design performances. Yannou et al (2009) and He et al (2012) showed how to identify a series of key variables for featuring usage scenarios that influence performance and utility.…”
Section: Confirmation With the Literaturementioning
confidence: 99%
“…The concept of usage context in design engineering has been first introduced in the works of Green et al (2004Green et al ( , 2005Green et al ( , 2006 and Yannou et al (2009). Green et al have published three successive papers on the subject, with the goal of forming a comprehensive product design methodology that includes contextual factors.…”
Section: Usage In Engineering Researchmentioning
confidence: 99%